Risk foot in diabetic patients. Community intervention. Medical Office 176.Policlinico Hermanos Cruz - Rodríguez Pérez, Yanet; Parra Rodríguez, Kirenia; Palomino Sosa, Rosadelis; Pérez Montiller, Carlos Enrique (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: The risk foot is an essential diagnosis to avoid future injuries in the lower extremities, which means that it is urgent to focus medical work in the community towards the prevention of diabetic foot ulcer to avoid amputations and its complications. Objective: to apply an educational intervention on the risk foot in diabetic patients belonging to the medical office 176 of the Hermanos Cruz polyclinic, during the period 2020-2022. Methods: A quasi-experimental study of educational intervention was carried out. The universe was constituted by 80 patients diagnosed with diabetes mellitus type II, aged between 19 to 60 years, belonging to the medical office 176, Hermanos Cruz Polyclinic, and the sample by 39 diabetic patients dispensarized with risk foot factors, who met the inclusion criteria. The study had 3 stages: diagnosis, intervention and evaluation. Theoretical and empirical methods were used through a survey to determine the level of knowledge before and after intervention and statistical methods given in number, % and chi-square. Results: the predominant age group was over 60 years old, with a pre-university level of education. In the variants studied after the educational intervention, there was a statistically significant increase in knowledge about the concept of diabetes mellitus (X2 = 28.04), risk foot (X2 = 27.04), lesions (X2 =33.03), risk factors (X2 =30.04) and type of treatment (X2 =32.03). Conclusion: the effectiveness of an adequate educational intervention to increase knowledge about risk foot in diabetic patients was demonstrated.